Performance enhancement of heterojunction ZnO/PbS quantum dot solar cells by interface engineering. (15th November 2020) - Kumar, Sandeep; Upadhyay, Rohitash; Pradhan, Basudev
Graphical abstract: Highlights: Performance optimization of ZnO/PbS solar cells by controlling surface roughness. The size of ZnO NCs aggregation was tuned by varying binary solvent volume ratio. ZnO aggregation having surface roughness close to size of PbS QDs performs better. Enhanced performance is attributed to improved junction interface contact. This approach of interface engineering can be adopted for other QDs based systems. Abstract: Effective charge transport through heterojunction interface in Quantum dots (QDs) based solar cells is difficult due to the spherical structure of QDs. Therefore tuning of QDs size for uniform and defect free heterojunction interface becomes very important to get optimum device performance. Here we have optimized the performance of ZnO Nanocrystals (NCs)/lead sulfide (PbS) QDs heterojunction solar cell by controlling the surface roughness of ZnO NCs thin films. The synthesized ZnO NCs aggregation was tuned by varying the binary solvent volume ratio of chloroform and methanol (CF:MeOH), which leads to the different surface roughness. The thin film of ZnO NCs having surface roughness comparable to the size of PbS QDs performs better as compared to those devices having different surface roughness. The optimum device fabricated in an ambient atmosphere with ZnO NCs thin film having surface roughness 4.36 nm, and nanocrystal size 3.32 nm as synthesized with (CF:MeOH) volume ratio of (2:1), shows the highest efficiency of 2.94% among other devices in the same structure due to decreased leakage current and improved junction interface contact between active materials. This work reveals that the controllability of ZnO NCs surface roughness and its correlation with the size of QDs can contribute to further improvement of low cost QDs based solar cells.